Tissue factor activity in women with preeclampsia or SGA: a potential explanation for the excessive thrombin generation in these syndromes. (18th June 2018) - Erez, Offer; Romero, Roberto; Vaisbuch, Edi; Than, Nandor Gabor; Kusanovic, Juan Pedro; Mazaki-Tovi, Shali; Gotsch, Francesca; Mittal, Pooja; Dong, Zhong; Chaiworapongsa, Tinnakorn; Kim, Chong Jai; Nhan-Chang, Chia-Ling; et al.
Abstract: Objective: The aim of this study was to determine whether the activity of tissue factor (TF) and tissue factor pathway inhibitor (TFPI) in the plasma of women with preeclampsia (PE) and small for gestational age (SGA) neonate differ from that of normal pregnant women and whether they are related to specific placental lesions. Methods: This cross-sectional study included the following groups: (1) normal pregnancy ( n = 68); (2) PE ( n = 128); and (3) SGA ( n = 56). Maternal plasma TF and TFPI activity was determined with chromogenic assays. Results : (1) The median maternal plasma TF activity, but not TFPI activity, differed among the study groups ( p < .0001 and p = .4, respectively); (2) patients with PE had a higher median maternal plasma TF activity than women with normal pregnancies ( p < .0001) and mothers with SGA fetuses ( p = .002); (3) among patients with PE, those with distal villous hypoplasia had a higher median maternal TF activity than those without these placental lesions ( p = .018); and (4) following adjustment for confounding variables, maternal plasma TF and TFPI activity were not associated with an SGA neonate. Conclusions: Plasma TF activity is higher in women with PE than in those with SGA or normal pregnancies. We propose that these changes may be responsible, at least in part, for the increased in-vivo thrombin generation observed in this obstetrical syndrome.